Will extreme weather events influence the toxic impacts of caffeine in coastal systems? Comparison between two widely used bioindicator species. (June 2022) - De Marchi, L.; Vieira, L.R.; Intorre, L.; Meucci, V.; Battaglia, F.; Pretti, C.; Soares, A.M.V.M.; Freitas, R.
Abstract: In the recent years, marine heatwaves (MHWs) have caused devastating impacts on marine life. The understanding of the combined effects of these extreme events and anthropogenic pollution is a vital challenge. In particular, the combined effect of MHWs on the toxicity of pharmaceuticals to aquatic life remains unclear. To contribute to these issues, the main goal of the present investigation was to evaluate how MHWs may increase caffeine (CAF) toxicity on the clam Ruditapes philippinarum and the mussel Mytilus galloprovincialis . Bioaccumulation levels and changes on oxidative stress, metabolic capacity and neurotoxic status related biomarkers were investigated. The obtained results revealed the absence of CAF accumulation in both species. However, the used contaminant generated in both bivalve species alteration on neurotransmission, detoxiﬁcation mechanisms induction as well as cellular damage. The increase of antioxidant defence mechanisms was complemented by an increase of metabolic activity and decrease of energy reserves. The obtained results seemed magnified under a simulated MHWs, suggesting to a climate-induced toxicant sensitivities' response. On this perspective, understanding of how toxicological mechanisms interact with climate-induced stressors will provide a solid platform to improve effect assessments for both humans and wildlife. Graphical abstract: Image 1 Highlights: Greater impacts in contaminated bivalves under marine heatwave (MHW) treatment. Higher metabolism in the presence of caffeine. Increased antioxidant defences and cellular damage in contaminated bivalves. Increased biotransformation capacity in mussels and clams exposed to caffeine. Neurotoxicity caused by caffeine, especially at MHW treatment.